Accumulation and associated phytotoxicity of novel chlorinated polyfluorinated ether sulfonate in wheat seedlings. (June 2020) - Lin, Qingqi; Zhou, Can; Chen, Lei; Li, Yafei; Huang, Xiongfei; Wang, Shizhong; Qiu, Rongliang; Tang, Changyuan
Abstract: Novel alternatives of perfluorooctane sulfonate (PFOS), chlorinated polyfluorinated ether sulfonates (Cl-PFAESs) are increasingly being detected in the aquatic and terrestrial environment. Previous studies mainly focused on aquatic biota; however, the knowledge about the ecotoxicological risk they pose to terrestrial plants was still lacking. In this study, the accumulation of two Cl-PFAES (6:2 and 8:2 Cl-PFAES) and PFOS in wheat seedlings at environmentally relevant levels (50 and 100 μg L −1 ) was investigated. Concentrations of Cl-PFAESs in the roots were an order of magnitude higher than those in shoots, indicating that they were primarily accumulated in the roots. The values of root and shoot bioconcentration factor was comparable between 6:2 Cl-PFAES and PFOS. However, these indexes of 8:2 Cl-PFAES were 42–91% higher and 70–76% lower than PFOS, respectively. As a result, 6:2 Cl-PFAES had a similar accumulation pattern as PFOS, whereas 8:2 Cl-PFAES was predominantly restricted to the roots, which might be attributed to their hydrophobicity and carbon chain length. In addition, at 250 mg L −1 of Cl-PFAESs, plant biomass and pigment content were 24–30% and 0.4–18%, respectively, which were lower than those of PFOS. As compared with PFOS, Cl-PFAESs induced higher levels of root membrane permeability, reactive oxygen species and malondialdehyde content, as well as reduced the activities of antioxidant enzymes and glutathione content. These suggested the occurrence of a severer oxidative damage and the breakdown of the antioxidant defence system in wheat cells. Therefore, we conclude that Cl-PFAESs might pose a higher potential threat to the environment than PFOS. Graphical abstract: Image 1 Highlights: Accumulation of Cl-PFAEs in wheat increased with increasing exposure level. Cl-PFAESs were mainly accumulated in roots and little was transferred to the shoots. 8:2 Cl-PFAES tended to accumulate in the roots more than 6:2 Cl-PFAES. The oxidative damage induced by Cl-PFAESs to wheat was more serious than PFOS.